The changing face of Hong Kong : new departures in public policy - Rabushka, Alvin (Washington DC: American Enterprise Institute for Public Policy Research, 1971)
This book provides a history of Hong Kong, its post-war economic development, the nature of its government, in the light of an unencumbered free enterprise political economy.
Includes bibliographical references.
lje 14/05/2018
Loans
Keywords: Economic history; Social conditions; Urbanization; Physical geography; City planning; Hong Kong (China); China